PENGARUH KEBERADAAN ANGGOTA DEWAN WANITA TERHADAP AGRESIVITAS PAJAK - Rakai Wastu Demos; Dul Muid (Diponegoro Journal of Accounting, 2020)
The purpose of this research is to examine the influence of female board members with tax aggressiveness. Independent variables used in this research are the presence of female inside board of directors and the presence of female inside board of supervisors. Dependent variable in this research is tax aggressiveness. This research used four control variables, they are profitability, leverage, company size, and board ownership.This research population was manufacture companies listed on Indonesian Stock Exchange during 2015-2018. The sample of the research is chosen by using purposive sampling method. Total samples used in this study as many as 51 companies. Data then analyzed using ordinary least square regression. This research showed that the presence of female board of directors members are positively and insignificantly related to tax aggressiveness. Meanwhile the presence of female board of supervisors members are negatively and insignificantly related to tax aggressiveness.